Performance enhancement of AlGaN-based deep ultraviolet light-emitting diodes by using stepped and super-lattice n-type confinement layer. (May 2020) - Liu, Nana; Gu, Huaimin; Wei, Ying; Zheng, Shuwen
Abstract: In this paper, a new n-type confinement layer that uses the stepped and super-lattice structure to replace conventional n-type AlGaN layer of deep ultraviolet light-emitting diode (DUV LED) is investigated. The simulation results indicate that the new structure significantly enhances the light output power (LOP) and internal quantum efficiency (IQE) of DUV LED. This is because the capability of carrier confinement in the quantum wells (QWs) is enhanced; the carrier concentrations and the radiative recombination rate in the active region of DUV LED are improved. Highlights: An innovative DUV LED with the stepped and super-lattice n-type confinement layer is proposed. The innovative DUV LED shows higher overlap of electrons and holes in its active region. The innovative DUV LED exhibits higher radiative recombination rate in the active region.